2019
DOI: 10.1177/1079063219825869
|View full text |Cite
|
Sign up to set email alerts
|

Excusing and Justifying Rape Cognitions in Judgments of Sexually Coercive Dating Scenarios

Abstract: According to recent analyses, Bumby’s RAPE scale of rape-supportive cognitions about women and sexual assault comprises two factors. Excusing rape serves to reduce abusers’ culpability for their offending, and ascribing blame to victims, while justifying rape is associated with a sense of sexual entitlement. The distinct effects of these factors on rape judgments have not yet been investigated. We examined whether these belief clusters differentially explained judgments of perpetrator innocence after priming c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 51 publications
3
11
0
1
Order By: Relevance
“…In addition, seeing the victims of revenge pornography as being responsible for their experiences was associated with greater levels of victim blame and lower rates of perceived criminality and victim harm (irrespective of their previous online posting activity). This is consistent with broader work in the area of sexual offending, where victim blaming and other offense-supportive cognitions are associated with a host of undesirable outcomes, including increased rates of sexual aggression proclivity and more lenient judgements of offense case studies (Bohner et al, 2005;Harper, Franco et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In addition, seeing the victims of revenge pornography as being responsible for their experiences was associated with greater levels of victim blame and lower rates of perceived criminality and victim harm (irrespective of their previous online posting activity). This is consistent with broader work in the area of sexual offending, where victim blaming and other offense-supportive cognitions are associated with a host of undesirable outcomes, including increased rates of sexual aggression proclivity and more lenient judgements of offense case studies (Bohner et al, 2005;Harper, Franco et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…Our motivation in doing so was rooted in the existing literature either using brief measures of judgements about revenge pornography offending (Bothamley & Tully, 2018;Fido et al, 2019) or not using transparent and systematic measures of scale development (Powell et al, 2019). Given the importance of offense-supportive cognition in contributing to both a proclivity towards and judgements of sexual offending (Bohner et al 2005;Harper, Franco et al, 2020;Hermann, et al, 2012Hermann, et al, , 2018 The systematic validation of the BRPQ identified several predictors of each cluster of beliefs, as well as establishing the measure's predictive validity itself. Endorsing rape myths was a substantial predictor of viewing revenge pornography victims as being responsible for their experiences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-perceived risk is a more difficult topic to assess indirectly. With the launch of new technologies allowing the embedding of indirect measures to online surveys (e.g., the iatgen applet extension, which facilitates the use of the implicit association test in surveys created using Qualtrics; Carpenter et al, in press), it might be possible to examine implicit levels of acceptance of child-adult sexual relationships in a manner similar to how implicit judgements of rape cases have been examined (e.g., Harper, Franco, & Wills, 2019). Another more straightforward alternative would be to use Gannon and O'Connor's (2011) Interest in Child Molestation scale, which explicitly asks respondents to rate (1) how aroused they might be if they were to put themselves in the position of a fictitious child sex offender, (2) whether they would do the same as this fictitious offender, and (3) the extent to which they would enjoy behaving in that manner.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%